The Influence Of Transparency, Participation And Accountability Of Village Fund Management In Seluma Regency - Alfajar, Muhammad Imam; Fitriano, Yun; Kresnawati, Kresnawati (Utami Publisher, 2025)
The principles of accountability and transparency also play a role in determining the level of public services for the community and measuring development. This study aims to determine the influence of Transparency, Participation, Accountability, and Village Fund Management Performance of Village Apparatus on Village Fund Management in Seluma Regency. The data in this study are primary data obtained from distributing questionnaires directly to village officials. The population in this study were 182 villages spread across Seluma Regency. While the sample of this research is 182 villages in Seluma Regency by taking 1 respondent in each village. The respondents chosen were village heads who were considered to be the most familiar with village management. The sampling technique was carried out using the random sampling method. Data were analyzed using Multiple Linear Regression analysis. From the results of the tests that have been carried out, it is stated that transparency (X1) has no significant effect. Participation (X2) and accountability (X3) have a positive and significant effect on the village funds management. While simultaneously, transparency, accountability, and have a positive and significant influence on village fund management.